Development of multiplex MPN-PCR To detect major vibrio species in raw fish and sushi / Sharmin Quazi Bonny - Sharmin Quazi , Bonny (2018)
Fish and fish products, the second most important source of protein after meat, constitute an important part in the international trade and incessantly exposed to an extensive range of microorganisms present in the environment. Among them Vibrio parahaemolyticus, Vibrio cholerae and Vibrio vulnificus are three most notorious aquatic pathogens causing a wide range of diseases in humans. However, the occurrence of these three pathogenic Vibrios in Malaysian raw fishes and ready-to-eat (RTE) fish products namely, sushi has not been thoroughly investigated. The most-probable number-PCR (MPN-PCR) assays had been reported to be highly sensitive for the identification of a single bacterial pathogen but they have not been applied for the enumeration of major Vibrios in a multiplex platform. Therefore, this study has coupled MPN method with Multiplex PCR to differentiate three major Vibrios in one single test. A total of 120 raw fishes were analyzed using optimized multiplex PCR, simplex MPN PCR and the developed Multiplex MPN-PCR approaches in order to compare the sensitivity of these three methods through determining the occurrence of V. parahaemolyticus, V. cholerae and V. vulnificus. The developed multiplex MPN-PCR was applied to examine the occurrence of these target Vibrios in 70 sushi samples. The microbial loads of the target Vibrios in sushi were recorded in three different time and conditions to determine microbial survivability upon storage at room temperature and after the recommended 7 days of refrigeration period. The developed Multiplex MPN PCR was found to be more sensitive compare to the Multiplex PCR. Besides, a rise in microbial load was recorded after leaving the sushi for 4-5 hrs. at the room temperature while the recommended 7-days refrigeration period reduced the bacterial growth but could not make the sushi entirely free of the pathogens. To conclude, combination of MPN and multiplex PCR assay was found significantly beneficial to achieve quantitative detection of multiple species in a single assay platform. Furthermore, the high prevalence of target Vibrios in edible raw fishes (27-48%) and sushi (4-28%) indicate considerable risk of Vibrios onset in Malaysia due to consumption of undercooked or raw fish and contaminated sushi.